2004
DOI: 10.1111/j.1467-629x.2004.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Technological and organizational influences on the adoption of activity‐based costing in Australia

Abstract: The present paper examines one set of potential reasons for the paradox as to why so few firms have adopted activity-based costing (ABC) despite the demonstrated benefits of this costing system. A cross-sectional survey of Australian firms is used to examine the influence of seven technological and organizational factors on firms' initial interest in ABC and their decision to adopt it or not. The organizational factors of top management support, the support of an internal champion, and organizational size were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
168
1
10

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(186 citation statements)
references
References 20 publications
7
168
1
10
Order By: Relevance
“…However, the researchers have developed various interpretative perspectives to know and highlight the factors affecting ABC adoption and implementation (Shield, 1995;Swenson, 1995;Malami, 1999;Maelah & Ibrahim, 2006) and the stages of its implementation processes (Anderson, 1995;Krumwiede, 1998;Brown, Booth & Giacobbe, 2004). However, most of these studies arrived to ambiguous, different and divergent results.…”
Section: Introductionmentioning
confidence: 99%
“…However, the researchers have developed various interpretative perspectives to know and highlight the factors affecting ABC adoption and implementation (Shield, 1995;Swenson, 1995;Malami, 1999;Maelah & Ibrahim, 2006) and the stages of its implementation processes (Anderson, 1995;Krumwiede, 1998;Brown, Booth & Giacobbe, 2004). However, most of these studies arrived to ambiguous, different and divergent results.…”
Section: Introductionmentioning
confidence: 99%
“…Many field studies and surveys demonstrated that the adoption of ABC tend to be more frequent in large organizations (Innes and Mitchell, 1995;Bjornenak, 1997;Malmi, 1999;Krumwiede, 1998;Pierce and Brown, 2004;Armitage and Nicholson, 1993;Innes et. al., 2000, Gosselin, 2007Brown et al 2001;Groot, 1999). Α possible reason for this is that larger organizations have relatively greater access to resources to experiment with the introduction of more sophisticated accounting systems.…”
Section: Sizementioning
confidence: 99%
“…However, this research has been somewhat fragmented because of the different ways in which it has defined the extent to which operating units have or have not adopted ABC (see Brown et al, 2004). This is illustrated below, which shows the different definitions of ABC adoption in research conducted in manufacturing industry.…”
Section: Introductionmentioning
confidence: 99%
“…Only Booth & Giacobbe (1998), Brown et al (2004) and Krumwiede (1998) have examined the issue of consideration for ABC. (Note 2) Booth & Giacobbe (1998) compared operating units with an interest in ABC (or those who were at least willing to consider it) to those that had not considered ABC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation